Cultural context and school counseling: Cultural sensitivity to advocate for social justice - Tatar, Moshé (2008)
In this paper the relevance of understanding the different meanings of culture in the counseling profession is presented. Two approaches to the concept of culture as they relate to counseling are suggested: the first approach stresses the organisational culture of the institution where the counselor works; the second —the multicultural approach— calls for the complex recognition of the variety of ethnic cultural backgrounds of those involved in the counseling situation. Professional practices are analysed as means for the reinforcement of present conditions or as ways for changing them. The concepts of empowerment of and advocacy for our clients are put forward as main components in the challenging new roles of the counseling profession. Implications for counselors are suggested.